Personal Near‐to‐Eye Light‐Field Displays. Issue 6 (1st November 2014) - Wu, Wanmin; Berkner, Kathrin; Tošić, Ivana; Balram, Nikhil
Abstract : In order for people to achieve true mobility – the ability to do anything, anywhere, anytime – there needs to be an entirely new class of mobile device.